Snail as mini-livestock: Nutritional potential of farmed Pomacea canaliculata (Ampullariidae) - Ghosh, Sampat; Jung, Chuleui; Meyer-Rochow, Victor Benno (Agriculture and Natural Resources, 2017)
Amino acids, fatty acids and minerals were investigated in the farmed freshwater snail Pomacea canaliculata (Ampullariidae) to understand its nutritional potential as alternative livestock. Snail samples with removed gut content were collected from a local snail farm in the Republic of Korea. Almost all the essential amino acids present in the snail protein satisfied the recommended level for an ideal protein pattern, while methionine was present at a marginal level. The proportion of unsaturated fatty acids (60.5%) was higher than that of saturated fatty acids (39.5%). The ratio of polyunsaturated to monounsaturated fatty acids was 1.08, underscoring the high nutritional quality of the fat content of the species. The most abundant mineral was calcium. The high K/Na ratio (3.9) and the presence of substantial amounts of phosphorus, iron and zinc makes P. canaliculata snail meat potentially valuable. Thus, the utilization of under-appreciated nutritious food resources could be helpful in mitigating food security problems and in solving nutritional shortcomings in underprivileged parts of the world.